COMPARATIVE ANALYSIS OF IN-STENT RESTENOSIS IN DIABETIC AND NON-DIABETIC PATIENTS UNDERGOING PERCUTANEOUS CORONARY INTERVENTION IN PAKISTAN - SHAH, T; VISHNO, HR; SHAH, SM; ULLAH, R (Biological and Clinical Sciences Research Journal, 2024)
Coronary artery disease (CAD) is a major global killer. Percutaneous coronary intervention (PCI) with drug-eluting stents (DES) has improved CAD treatment. However, in-stent restenosis (ISR) remains a significant issue, especially for diabetic patients. Objective: This study aimed to compare ISR rates between diabetic and non-diabetic patients after PCI in a Pakistani hospital. Methods: We conducted a cross-sectional survey at Hayatabad Medical Complex, Peshawar, from January to December 2023. The study involved 273 patients aged 40-85 who underwent PCI with DES. Participants were split into diabetic and non-diabetic groups. Those with chronic kidney disease, previous coronary artery bypass graft surgery, or incomplete follow-up data were excluded. Data were gathered from medical records. ISR was marked by a luminal diameter reduction of more than 50% within the stent or 5 mm of its edges. We used chi-square tests and logistic regression for analysis, employing SPSS version 26.0. Results: The ISR rate was 23% overall. Diabetic patients showed a higher ISR rate (30%) than non-diabetic patients (16%). Logistic regression revealed diabetes (OR = 2.1, 95% CI: 1.3-3.2, p < 0.01), hypertension (OR = 1.8, 95% CI: 1.1-2.9, p < 0.05), and smoking (OR = 1.6, 95% CI: 1.0-2.5, p < 0.05) as significant predictors of ISR. Conclusion: This study highlights a higher ISR incidence in diabetic patients post-PCI. It underscores the need for meticulous monitoring and tailored strategies for this high-risk group. Managing hypertension, smoking, and dyslipidemia is essential to lower ISR rates and enhance outcomes.